The Effect Of Budget Requirements And Management On The Performance Of Goods And Services Procurement System - Camelia Febryanti; Endah Suharlin Tanjung; Sila Insan Tikayani; Nur Afifah; Neng Sri Wardhani (CV. AFDIFAL MAJU BERKAH, 2024)
This research, therefore, has been done to investigate the influence of budget requirements and management on procurement for goods and service performance in the Indonesian system. In this study, the focus will be on how the organizational needs are met and how effective the management of budget resources is in the procurement system. Despite the improvement made on regulations, challenges remain on compliance in relation to the needs of procurement and budgetary constraints. This research applies a document analysis and literature review to qualitative approach the assessment of these factors. Findings from this study show the importance of the need for the precise identification of need, stakeholder involvement, and strong cost control mechanisms. Overcoming these challenges can significantly enhance procurement efficiency and effectiveness within organizations.